Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/polym15163398
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Regeneration at 1 Year: Biodegradable Polybutylene Succinate Artificial Scaffold vs. Conventional Epineurial Sutures

Abstract: The utilization of a planar poly(1,4-butylene succinate) (PBS) scaffold has been demonstrated as an effective approach for preserving nerve continuity and facilitating nerve regeneration. In this study, we assessed the characteristics of a microfibrous tubular scaffold specifically designed and fabricated through electrospinning, utilizing PBS as a biocompatible and biodegradable material. These scaffolds were evaluated as nerve guide conduits in a rat model of sciatic nerve neurotmesis, demonstrating both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Indeed, once the effect of 2D materials on the players involved in nerve regeneration is unravelled, it would be possible to integrate the materials onto a biopolymer support to realize a planar polymeric structure rolled to form tubular nerve conduits. In the literature there are many examples of 3D tubes prepared from a planar scaffold that can be simply rolled along the lengthwise edge and taped, 122 implanted and wrapped directly around the nerve stumps 123 or prepared using self-rolling films. 124 Similar examples are also between FDA-approved nerve grafts, such as NeuraWrap™ (Integra LifeSciences Co.) that is used by wrapping around the injured nerves, or NeuroMend™ (Collagen Matric, Inc.) that can be unrolled and self-curled to match the dimensions of the injured tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, once the effect of 2D materials on the players involved in nerve regeneration is unravelled, it would be possible to integrate the materials onto a biopolymer support to realize a planar polymeric structure rolled to form tubular nerve conduits. In the literature there are many examples of 3D tubes prepared from a planar scaffold that can be simply rolled along the lengthwise edge and taped, 122 implanted and wrapped directly around the nerve stumps 123 or prepared using self-rolling films. 124 Similar examples are also between FDA-approved nerve grafts, such as NeuraWrap™ (Integra LifeSciences Co.) that is used by wrapping around the injured nerves, or NeuroMend™ (Collagen Matric, Inc.) that can be unrolled and self-curled to match the dimensions of the injured tissue.…”
Section: Discussionmentioning
confidence: 99%
“…et al [37] demonstrated improved bone regeneration using an artificial polybutylene succinate scaffold in a rabbit model. This scaffold has already been employed for nerve regeneration in a murine model [38,39]. This application could potentially be considered in the future for cases of bilateral scaphoid fractures in cases not suitable for performing an autologous graft harvesting procedure [40].…”
Section: Discussionmentioning
confidence: 99%